2015
DOI: 10.1007/s13277-015-3988-8
|View full text |Cite
|
Sign up to set email alerts
|

BMP pathway suppression is an early event in inflammation-driven colon neoplasmatogenesis of uPA-deficient mice

Abstract: The suppression of the bone morphogenetic protein (BMP) signaling pathway has been recently shown to promote adenoma-to-carcinoma transition in sporadic colon cancer. However, its role in the evolution of early preneoplastic changes to neoplasia remains elusive. In the present study, we aimed to investigate the gene expression levels of multiple extracellular BMP family constituents, including BMP ligands/receptors and inhibitors, during the early stages of inflammation-associated colon carcinogenesis. For tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…A recent report indicated that β-catenin can be inhibited by BMP via SMAD4 to down-regulate the expression of c-myc and Axin2 in microdissected small intestinal adenomas of tamoxifen-treated mice [98]. Another study sufficiently suggests that BMP and WNT appear to be interconnected via the PI3k/Akt pathway [99,100].…”
Section: Bone Morphogenetic Protein (Bmp)/smad Pathways As Important mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report indicated that β-catenin can be inhibited by BMP via SMAD4 to down-regulate the expression of c-myc and Axin2 in microdissected small intestinal adenomas of tamoxifen-treated mice [98]. Another study sufficiently suggests that BMP and WNT appear to be interconnected via the PI3k/Akt pathway [99,100].…”
Section: Bone Morphogenetic Protein (Bmp)/smad Pathways As Important mentioning
confidence: 99%
“…Subsequently, activated p-SMAD 1/5/8 translocates from the cytoplasm to the nucleus by forming a complex with SMAD4, and ultimately, it regulates transcription and expression of target genes such as inhibitor of DNA binding (ID) [96] and CCL15 [97]. Importantly, the BMP pathway is down-regulated in the majority of colon cancer cases [98].…”
Section: Bone Morphogenetic Protein (Bmp)/smad Pathways As Important mentioning
confidence: 99%
“…5,12,13 So we also detected the effect of tumor-secreted GREM1 on the capillary structure formation of HUVEC. 5,12,13 So we also detected the effect of tumor-secreted GREM1 on the capillary structure formation of HUVEC.…”
Section: Crc-induced Capillary Structure Formation and Viability Of Hmentioning
confidence: 99%
“…Previous studies demonstrated that Gremlin1 is overexpressed in various types of human cancers [26]. It has been reported that Gremlin1 is associated with tumorigenesis of several cancers, including oral cancer, glioma, colorectal cancer, hepatocellular cancer and renal cancer [22,[27][28][29][30][31][32][33].…”
Section: Ivyspring International Publishermentioning
confidence: 99%